Is the mathematics classroom a suitable learning space for making workplace mathematics visible? - An analysis of a subject integrated team-teaching approach applied in different learning spaces - Frejd, P.; Muhrman, K. (Journal of vocational education & training, 2022)
This article presents an analysis of a team-teaching approach, applied in two learning spaces: a regular mathematics classroom; and a hairdressing salon at an upper secondary vocational education and training (VET) school. A mathematics teacher and a VET teacher jointly developed, planned and carried out the teaching activities in these two learning spaces. The overall goal was to prepare their 15 students for professional life. Observations made from the two lessons were analysed with the aim of identifying the extent to which the outcome of the team-teaching approach is dependent on the choice of the learning space. Drawing on Engeström's activity theory and research literature on learning spaces, our results indicate that tools, norms, division of labour and community differ significantly within the two learning spaces. The environment of the salon appeared to be more effective in promoting discussion, and encouraging self-confidence and identity-making, in comparison with the mathematics classroom, and there was a more visible interaction between mathematics and vocational subjects. This raises questions about the optimal design of the applied team-teaching approach and about whether the mathematics classroom can be considered a suitable learning space for facilitating students' learning of workplace mathematics.